VHDL a starter's guide - Yalamanchili, Sudhakar (Pearson/Prentice Hall, 2005)
This companion text enables instructors to integrate the basic concepts of VHDL into existing courses. It is designed to develop an intuition and a structured way of thinking about VHDL models without spending a great deal of time on advanced language features.